Safety index for agricultural tractors - Oldoni, André; Spagnolo, Roger Toscan; Morais, César Silva de; Rocha, Marco Aurélio Nunes da; Machado, Antônio Lilles Tavares; Reis, í‚ngelo Vieira dos (Acta Scientiarum. Technology, 2017)
The manufacture of agricultural machinery should follow the criteria that specify the existence and standardization of components and security systems, so as to make them safe. The aim of this study was to establish a checklist to classify agricultural tractors according to a safety index. The list was obtained through literature review and by checking norms and articles on Components and Security Systems (CSSs) that must be present on tractors in order to provide proper security. These CSS were grouped to form a checklist obtained by the Mudge diagram, whose function was to pair CSSs according to their relevance in order to organize them hierarchically. Subsequently, a spreadsheet with weighted CSSs was applied to 31 tractor models of 5 different brands, enabling the determination of their safety ratings by the addition of values of each CSS. A CSS checklist allowed obtaining a safety index listing tractors by the level of safety offered by each of them, thus enabling the tractor buyer to choose the one that offers lower risk of accidents in its use. Â